Transformasi Media Relations di Era Digital: Studi Kasus di Indonesia - Andri Kurniawan; Syfa Solehah Barata (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The current digital landscape is driving new ways of thinking and methods for managing information in communication with mass media. Mass media, which was once considered effective in shaping public opinion as part of public relations strategies through media relations, now faces a range of challenges. The rise of new professions, such as brand reviewers through Key Opinion Leaders (KOLs) and influencers, the emergence of artificial intelligence (AI), and Homeless Media and the large number of layoffs in the media industry became a phenomenon and challenges that cannot be ignored in the role of mass media today. However, despite these challenges, mass media, as the fourth pillar of democracy, continues to strive to maintain its existence amidst the noise by presenting the "true voice." This study aims to explore in greater depth the challenges and opportunities of building relationships with mass media (media relations) in the digital era, using a qualitative descriptive research approach.